Direct Impact of Human Platelets on the Development of Transplant Arteriosclerosis. - Görner, Susann; Heim, Christian; Weigmann, Benno; Von Silva-Tarouca, Benjamin; Kuckhahn, Annika; Ramsperger-Gleixner, Martina; Zimmermann, Robert; Weyand, Michael; Ensminger, Stephan M. (Transplantation, 2022)
BACKGROUND: Platelets play an important role in the pathogenesis of inflammatory and proliferative vascular changes. The aim of this study was to investigate whether human platelets are able to induce transplant arteriosclerosis in a humanized C57/Bl6-Rag2-/-γc-/- mouse xenograft model. METHODS: Nonactivated and in vitro-activated human platelets were analyzed and phenotyped for surface markers by flow cytometry. Side branches of human mammary arteries were implanted into the infrarenal aorta of recipients, followed by daily application of human platelets and histological analyzed on day 30 after transplantation. RESULTS: Human platelets collected by apheresis had low levels of platelet activation markers. However, after in vitro activation, expression was markedly increased. Sixty minutes after injection in recipient mice, nonactivated human platelets become significantly activated. Increased adhesion of platelets to the vascular endothelium was detected by in vivo fluorescence microscopy. After intravenous injection of nonactivated or activated platelets, human xenografts showed pronounced intimal proliferation. Immunohistological analysis showed that the group treated with activated human platelets exhibited significantly increased intragraft protein expression of intracellular adhesion molecule-1 and platelet-derived growth factor receptor beta and smooth muscle cell migration into the neointima. CONCLUSIONS: These data demonstrate that an isolated daily application of both in vivo- and in vitro-activated human platelets results in the development of transplant arteriosclerosis in a humanized mouse transplantation model.
EVALuna2:473994